Optimalisasi Penerbitan Surat Berharga Syariah Negara (SBSN) Pada Indstri Keuangan Syariah - Alif Rodliya Wahid (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2019)
State Sukuk (Surat Berharga Syariah Negara) is an instrument of investment activities issued by the government. Sukuk can be used as a development of infrastructure that is primarily focused on advancing the nation’s economy and creating public welfare. This research was conducted in the form of descriptive analysis. This study describes and interprets the condition of the development of sukuk for five years starting from 2013 to 2017. State Sukuk as a form of investment issued by the government has several benefits. First, the State Sukuk as an alternative to financing the state budget deficit, and an alternative investment for investors who want to manage their funds sharply. The two State Sukuk can also enrich the effects of sharia traded on the Islamic capital market so that they can develop, strengthen and enhance the role of the sharia-based financial system in the country. Thirdly, creating benchmarks of Islamic financial instruments on the domestic and international financial markets. The four State Sukuk can be used as a form of financing infrastructure projects and optimize the use of State Property (BMN).